Encyclopedia of sociology (New York : Macmillan, 2001)
This classic reference has been updated to reflect many changes in society and in the field of sociology in recent years. Articles covering core issues such as race, poverty, violence, economics, pregnancy and abortion have been updated and expanded, and completely new articles have been written on topics such as the Internet, privacy and epidemiology.
Ηλεκτρονικό βιβλίο
Keywords: Sociology -- Encyclopedias; Electronic books